1992
DOI: 10.1007/bf00133722
|View full text |Cite
|
Sign up to set email alerts
|

Genome canalization: the coevolution of transposable and interspersed repetitive elements with single copy DNA

Abstract: Transposable and interspersed repetitive elements (TIREs) are ubiquitous features of both prokaryotic and eukaryotic genomes. However, controversy has arisen as to whether these sequences represent useless 'selfish' DNA elements, with no cellular function, as opposed to useful genetic units. In this review, we selected two insect species, the Dipteran Drosophila and the Lepidopteran Bombyx mori (the silkmoth), in an attempt to resolve this debate. These two species were selected on the basis of the special int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 208 publications
(264 reference statements)
1
53
0
Order By: Relevance
“…This is not surprising however, when considering the difference in genome organization of mammals and Drosophila (von Sternberg et al 1992). The Drosophila genome is quite compact as exemplified by the 1 kb Dhfr gene with a lone 50 bp intron and a single TATA sequence for transcription initiation (Hao et al 1994).…”
Section: Dihydrofolate Reductase From Drosophila and Mammalsmentioning
confidence: 99%
“…This is not surprising however, when considering the difference in genome organization of mammals and Drosophila (von Sternberg et al 1992). The Drosophila genome is quite compact as exemplified by the 1 kb Dhfr gene with a lone 50 bp intron and a single TATA sequence for transcription initiation (Hao et al 1994).…”
Section: Dihydrofolate Reductase From Drosophila and Mammalsmentioning
confidence: 99%
“…However, the question of whether transposable elements are just ''junk'' DNA to the host, or whether they can play important and even adaptive roles in organismal evolution, is currently actively debated (e.g., refs. 6, 12, 14-17, and [55][56][57][58].…”
Section: Mite-like Elements and The Size And Organization Of Eukaryotmentioning
confidence: 99%
“…Once in heterochromatin, genes would have been targeted by recurrent insertions of transposable elements, thus generating the present structural organization. Transposable element-related sequences in heterochromatin might thus contribute, in ways that are still poorly understood, to many of the structural and functional properties of heterochromatin, including the regulatory evolution of these genes (Pimpinelli et al, 1995;Weiler and Wakimoto, 1995;Dimitri, 1997;Dimitri and Junakovic, 1999;Yasuhara et al, 2005), similar to documented instances found in euchromatin (Von Stenberg et al, 1992;Miller et al, 1999;Kidwell and Lish, 2000;Jordan et al, 2003;Brandt et al, 2005;Kapitonov and Jurka, 2005). Over evolutionary time, transposable elements can thus be viewed as 'artisans' that have shaped heterochromatin, rather than merely as parasitic sequences (Dimitri et al, 2005b).…”
Section: Melanogaster Heterochromatic Genes In Other Speciesmentioning
confidence: 98%